Persepsi Pengusaha Muda Terhadap Kesuksesan Menjalankan Bisnis Start-Up - Riwanda, Fany; Mawarpury, Marty (Psychopreneur Journal, 2021)
Abstract: Perception of success is an individual’s perspective on something related to a meaningful life orientation. A person’s perception of success is subjective to each individual. Young business owners have their own criteria about a successful business, thus making the meaning of success different.The purpose of this study is to see how entrepreneurs perceive the success of the business they have lived. Respondents in this study are two Acehnese entrepreneurs who have start-up businesses. Research data obtained through in-depth interviews conducted on each respondent. The questions are structured based on the theory of Perception of Success. The results of the interview show that success is viewed differently according to the meaning of success itself for each individual. Respondent I views a successful business as a wholesome, both from the point of view of the entrepreneur and the company. Meanwhile, respondent II perceive succes as how much profit is obtained, popularity, and job providers. Keywords: perception of success, start-up, success Abstrak: Perception of success merupakan cara pandang individu terhadap sesuatu hal terkait dengan orientasi kehidupan yang bermakna. Persepsi seseorang tentang kesuksesan adalah subjektif pada masing-masing individu. Para pebisnis muda memiliki kriterianya masing-masing terhadap kasuksesan sebuah bisnis, sehingga menjadikan makna sukses berbeda-beda. Tujuanpenelitian ini adalah untuk melihat bagaimana persepsi pengusaha terhadap kesuksesan bisnis yang telah dijalaninya. Responden pada penelitian ini berjumlah dua orang pengusaha Aceh yang memiliki bisnis start-up. Data penelitian didapatkan melalui wawancara mendalam yang dilakukan pada masing-masing responden. Perntanyaan wawancara disusun berdasarkan teori Perception of Success. Hasil wawancara menunjukkan bahwa kesuksesan dipandang secara berbeda-beda sesuai dengan pemaknaan kesuksesan itu sendiri bagi setiap individu. Responden I memandang sebuah bisnis yang sukses secara keseluruhan, baik dari sudut pandang pengusaha ataupun perusahaannya. Sedangkan responden II memandang kesuksesan dari seberapa besar keuntungan yang diperoleh, popularitas, dan penyediakan lapangan pekerjaan. Kata kunci: perception of success, start-up, kesuksesan